REAKTUALISASI KONSEP SAPRAH AMAL SEBAGAI SUMBER KEUANGAN PUBLIK ISLAMâ STUDI: SAPRAH AMAL DI MENDAWAI KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Syarifuddin, Syarifuddin; Sadikin, Ali; Nordin, Muhammad (AL-QARDH, 2016)
One of tradition effort in a Muslim community, especially in Mendawai area is to innovate in economic activities which is mutual cooperation to increase mutual prosperity by establishing SaprahAmal (Charity) as innovation or alternative in to build Muslim facilities. This alternative is often performed by the community, not only on buying or selling activity but SaprahAmal also teaches to share with others to achieve a goal that the community expects in order to achieve falah (success, happiness and well-being).